A Systematic Review and Meta-Analysis of School-Based Stress, Anxiety, and Depression Prevention Programs for Adolescents. - Feiss, Robyn; Dolinger, Sarah Beth; Merritt, Monaye; Reiche, Elaine; Martin, Karley; Yanes, Julio A.; Thomas, Chippewa M.; Pangelinan, Melissa (Journal of Youth & Adolescence, 2019)
Given the recent rise in adolescent mental health issues, many researchers have turned to school-based mental health programs as a way to reduce stress, anxiety, and depressive symptoms among large groups of adolescents. The purpose of the current systematic review and meta-analysis is to identify and evaluate the efficacy of school-based programming aimed at reducing internalizing mental health problems of adolescents. A total of 42 articles, including a total of 7310 adolescents, ages 11–18, met inclusion for the meta-analyses. Meta-analyses were completed for each of the three mental health outcomes (stress, depression, and anxiety) and meta-regression was used to determine the influence of type of program, program dose, sex, race, and age on program effectiveness. Overall, stress interventions did not reduce stress symptoms, although targeted interventions showed greater reductions in stress than universal programs. Overall, anxiety interventions significantly reduced anxiety symptoms, however higher doses may be necessary for universal programs. Lastly, depression interventions significantly reduced depressive symptoms, but this reduction was moderated by a combination of program type, dose, race, and age group. Although, school-based programs aimed at decreasing anxiety and depression were effective, these effects are not long-lasting. Interventions aimed at reducing stress were not effective, however very few programs targeted or included stress as an outcome variable. Implications for practice, policy and research are discussed.